Elevated Mouse Hepatic Betatrophin Expression Does Not Increase Human β-Cell Replication in the Transplant Setting - Jiao, Yang (American Diabetes Association, 2014)
The recent discovery of betatrophin, a protein secreted by the liver and white adipose tissue in conditions of insulin resistance and shown to dramatically stimulate replication of mouse insulin-producing β-cells, has raised high hopes for the rapid development of a novel therapeutic approach for the treatment of diabetes. At present, however, the effects of betatrophin on human β-cells are not known. Here we use administration of the insulin receptor antagonist S961, shown to increase betatrophin gene expression and stimulate β-cell replication in mice, to test its effect on human β-cells. Although mouse β-cells, in their normal location in the pancreas or when transplanted under the kidney capsule, respond with a dramatic increase in β-cell DNA replication, human β-cells are completely unresponsive. These results put into question whether betatrophin can be developed as a therapeutic approach for treating human diabetes.